Consumption of Animal Source Foods Is Associated With Differences in Breastmilk Energy and Macronutrient Composition in Rural Bangladesh. (14th June 2022) - Andrews, Chloe; Olson, Ingrid; North, Krysten; Ahmed, Salahuddin; Rahman, Sayedur; Khanam, Rasheda; Baqui, Abdullah; Belfort, Mandy; Lee, Anne; Sen, Sarbattama
Abstract: Objectives: To quantify associations of maternal consumption of animal source foods during lactation with maternal milk (MM) energy and macronutrient composition in a population with a high burden of childhood stunting. Methods: We studied 99 mother-infant dyads from the Projahnmo pregnancy cohort in Sylhet, Bangladesh. Data on maternal diet was collected using a food frequency questionnaire administered at 1-month postpartum. Mothers reported how many times (never to daily) a food item was consumed in the past 7 days. We assessed intakes of red meat, liver, poultry, fish, eggs, and milk and milk products (sum of milk, yoghurt, milk powder, and khoa). Mothers collected their milk mid-feed at 1-month postpartum. True protein, fat, and total carbohydrate content of MM were determined using mid-infrared transmission spectroscopy (MIRIS AB, Uppsala, Sweden). Total energy was calculated using the Atwater general calorie conversion factor. To quantify associations of animal source food consumption with MM composition, we used linear regression analysis, adjusting for maternal body mass index, household wealth quintile, and days postpartum. Results: Median maternal age was 24 years. 31% of mothers were underweight and 15% were overweight/obese at enrollment. MM samples were collected at a median of 50 days postpartum. The median MM energy content was 22.9 kcal/oz. Median fat content was 4.7 g/dL, carbohydrate 7.8 g/dL, and protein 0.9 g/dL. In adjusted analyses, each serving/week of milk and milk products was associated with increased MM energy (β 0.33 kcal/oz; 95% CI 0.06, 0.60) and fat (β 0.13 g/dL; 95% CI 0.03, 0.23). Each serving/week of liver was associated with decreased carbohydrate (β −0.06 g/dL; 95% CI −0.11, −0.01) and increased protein (β 0.06 g/dL; 95% CI 0.02, 0.10) content. Each serving/week of red meat was associated with increased protein content (β 0.06 g/dL; 95% CI 0.01, 0.12). Intake of total animal source foods, poultry, fish, and eggs was not associated with MM composition. Conclusions: Intakes of some animal source foods were associated with MM composition at 1-month postpartum in rural Bangladesh. Increasing consumption of certain animal source foods during lactation could be an effective strategy to optimize MM composition, which may benefit infant growth outcomes in low-to-middle-income countries. Funding Sources: NICHD, Brigham Research Institute.